2017
DOI: 10.1128/aem.03187-16
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Virus Distribution in a Defined Swine Production Network Using Enteric Viruses as Molecular Markers

Abstract: Modern swine production systems represent complex and dynamic networks involving numerous stakeholders. For instance, livestock transporters carry live animals between fattening sites, abattoirs, and other premises on a daily basis. This interconnected system may increase the risk of microbial spread within and between networks, although little information is available in that regard. In the present study, a swine network composed of 10 finishing farms, one abattoir, and three types of stakeholders (veterinari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Porcine astroviruses (PoAstVs) are genetically diverse and are distributed worldwide [10] with five genetic lineages (PoAstV1-5), reflecting different origins, interspecies transmission and recombination events [9,11,12]. Globally, several studies have reported the molecular detection and genetic characterization of PoAstVs in various pig production systems in different countries including Canada [11,13], China [14,15,16], Croatia [17], Czech Republic [18], East Africa [19], Germany [20,21,22], Hungary [23], Italy [24], Japan [25], Slovakia [26], Sweden [27,28], South Korea [29], Thailand [30], and the United States [31,32,33,34,35,36,37]. However, the pathogenicity of a majority of PoAstVs is not well characterized with the exception of PoAstV3, which has been associated with polioencephalomyelitis in swine in both Europe [23] and the United States [31,32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine astroviruses (PoAstVs) are genetically diverse and are distributed worldwide [10] with five genetic lineages (PoAstV1-5), reflecting different origins, interspecies transmission and recombination events [9,11,12]. Globally, several studies have reported the molecular detection and genetic characterization of PoAstVs in various pig production systems in different countries including Canada [11,13], China [14,15,16], Croatia [17], Czech Republic [18], East Africa [19], Germany [20,21,22], Hungary [23], Italy [24], Japan [25], Slovakia [26], Sweden [27,28], South Korea [29], Thailand [30], and the United States [31,32,33,34,35,36,37]. However, the pathogenicity of a majority of PoAstVs is not well characterized with the exception of PoAstV3, which has been associated with polioencephalomyelitis in swine in both Europe [23] and the United States [31,32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that lettuces washed at the last stage of production do not represent a benefit for virus removal, since the waters used are also contaminated. Enteric viruses including EV have been used as indicators of sanitation and hygiene practices at food production sites on dairy and swine farms (Fongaro et al, 2014;Kokkinos et al, 2012;Lachapelle, Letellier, Fravalo, Brassard, & L'Homme, 2017;Maunula et al, 2013;Staggemeier et al, 2015;Yavarmanesh, Alum, & Abbaszadegan, 2015).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Odds ratio (OR): a ratio for the measure of association between exposure and outcome (Suzmilas et al, 2010); OR = 1 cases has no effect on detection of PoAstVs, OR < 1 odds of detection of PoAstVs among cases are greater than odds of detection of PoAstVs among controls, OR > 1 odds of detection of PoAstVs among cases are lower than odds of detection of PoAstVs among controls. Boros et al, 2017 RT-PCR PRRSV, PCV2, PHEV, PPV 1,2,4 and PBoV Goecke et al, 2017 RT-PCR RVA, RVC, TGEV, PEDV, PRCV, PSaV, PEV, Parechovirus, Saffoldvirus, Lachapelle et al, 2017 RT-PCR RVA Xiao et al, 2017 RT-PCR TGEV, PRRSV, PEDV, CSFV Kumthip et al, 2018 RT-PCR RVA, RVC Matias et al, 2018 Sequencing PRRSV 1 and 2, PCV2, Suid alphaherpesvirus 1, PTV, PSV, APPV Salamunova et al, 2018 RT…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%